Business research methods - Gupta S L; Gupta, Hitesh (New Delhi McGraw Hill Education, 2024)
About the Book: Business Research Methods "This book is designed to discuss in a lucid and easy-to-understand manner, the theory as well as applied aspects of business research. With many examples from the Indian context and a number of application exercises covering various research tools and techniques, it will fulfill the requirements of the students as well as teachers of the subject. Designed to serve primarily as a textbook for business management students, it will also be useful as reference book by practicing managers and researchers in various fields." Contents 1. Business Research: An Overview 2. Research Methods, Problems and Hypothesis 3. Business Research Designs 4. Methods and Techniques of Data Collection 5. Sampling 6. Attitude Measurement and Scales 7. Questionnaire Design 8. Data Preparation and Preliminary Analysis 9. Statistical Analysis and Interpretation of Data 10. Multivariate Analysis 11. T- Test and Anova 12. Business Research Report and Proposal Writing
Keywords: Management